Efek Penggunaan Gadget Terhadap Perkembangan Bahasa Jawa Anak Usia Dini - Muhammad Ridwan; Sigit Wibowo; Akbar Setiawan; Nurnaningsih; R. Adi Deswijaya (Kawruh: Journal of Language Education, Literature and Local Culture, 2026)
The era of digital disruption presents complex challenges for the acquisition of mother tongue in early childhood (golden age), especially Javanese which has an upload-ungguh system. This study aims to describe the implications of gadget use on the influence of Javanese language development in children aged three to six (3-6) years in Karangayar Regency. This study uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation. Data analysis was conducted interactively to map children's speech and behavior patterns. The results show that high intensity of gadget use without supervision causes degradation of pragmatic abilities, which manifests in passive verbal responses, linguistic interference (code mixing), and imitation of aggressive diction from online content and games. However, positively, gadgets can potentially become instruments of cultural preservation if used to access educational content that enriches children's Krama Javanese lexicon. The conclusion of this study confirms that the role of parental mediation (digital parenting) is a determinant variable in maintaining the balance between digital literacy and ethics.